A clinical study of cutaneous lesions in neonates at a tertiary health care center in Chennai - Shilpa Gudurpenu; Aditya Kumar Bubna; Sudha Rangarajan; Mahalakshmi Veeraraghavan; Maharaja Krishnamoorthy; Gayathri Rajesh (Wolters Kluwer Medknow Publications, 2017)
Background: Neonatal dermatoses constitute an important category of cutaneous disorders. They range from physiological transient conditions at one end to serious pathological entities at the other. Any of these could be a source of immense anxiety to the parents, and therefore the significance of their adequate awareness amongst dermatologists. Aim and Objective: To study the clinical pattern of various dermatoses in neonates at a tertiary health care center in Chennai. Materials and Methods: This was a descriptive, cross-sectional, and observational study conducted at our institute which included a detailed dermatologic examination of each neonate followed by recording each finding and their statistical analysis. Results: In the 220 neonates analyzed, 97 were females (44.1%) and 123 males (55.9%), with 126 being term babies (57.3%), 86 preterm (39.1%), and 8 postterm (3.6%). Physiological skin changes (52.7%) were the most common cutaneous change identified, followed by transient non-infective dermatoses (20%), developmental defects (7.3%), birth marks (7.3%), eczema (6.8%) and infections (5.9%). Conclusion: Studying neonatal dermatoses holds significance to all dermatologists so that they are able to differentiate physiological and pathological conditions, thereby relieving unnecessary therapy for neonates in circumstances not requiring any and also facilitating to allay undue anxiety among parents.